2018
DOI: 10.1002/path.5017
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing of oral mucosal melanoma reveals mutational profile and therapeutic targets

Abstract: Oral mucosal melanoma (OMM) is a rare and aggressive subtype of melanoma with little known about its pathogenesis or carcinogenesis. We therefore performed whole-exome sequencing (WES) on 19 matched OMM tumor/normal pairs in order to gain insight into potential genetic drivers of tumor formation. For the first time, we describe the comprehensive mutational profile of OMM. Our data suggest that the genetic background of OMM differs from those of other melanoma subtypes. We identified recurrent mutations involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 39 publications
7
46
0
2
Order By: Relevance
“…22 (8,24,27,28) together with a sigmoidal trend (a complex alternation of copy number gains followed immediately by copy number losses), in CFA 10 and 30 (8,24,28). In this study, CFA 10 and CFA 30 also showed the sigmoidal trend, and 7 of the regions found imbalanced were already reported in recent literature (Tables 2A,C) (24); with an § the syntenic regions reported by Curtin et al (5); no regions were shared with Lyu et al (7).…”
Section: Comparison With Published Canine Cnassupporting
confidence: 80%
See 4 more Smart Citations
“…22 (8,24,27,28) together with a sigmoidal trend (a complex alternation of copy number gains followed immediately by copy number losses), in CFA 10 and 30 (8,24,28). In this study, CFA 10 and CFA 30 also showed the sigmoidal trend, and 7 of the regions found imbalanced were already reported in recent literature (Tables 2A,C) (24); with an § the syntenic regions reported by Curtin et al (5); no regions were shared with Lyu et al (7).…”
Section: Comparison With Published Canine Cnassupporting
confidence: 80%
“…Large chromosomal aberrations, known to be deeply involved in solid tumors development (9), were investigated in hMMs through numerous techniques. Up to date, promising recurrent regions of gains and losses were identified (5) and confirmed by several investigations (4,7,8), in particular amplified portions of HSA 12q and 5p, which encode for genes as CDK4 and TERT, respectively (7). In addition, CCND1, KIT, and VEGFRA were proposed by a recent review (10) as targets for future investigations.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations